Analisis Perbandingan Pengaruh Komunikasi Budaya dan Komunikasi Antarpribadi terhadap Niat Mengunjungi Event Kembali - Setiawan, Romi; Wibisono, Dermawan; Purwanegara, Mustika Sufiati (Jurnal Manajemen Indonesia, 2024)
This study explores the impact of regional cultural dynamics on event engagement and revisit intentions in Indonesia, focusing on differences between Java and Non-Java regions. Using Multigroup Analysis in Partial Least Squares Structural Equation Modeling (MGA-PLS), the study compares how differences in regional culture affect consumer behavior, going beyond the usual focus on differences in race. Results indicate no significant differences in the influence of cultural dynamics on event engagement between these regions, highlighting a uniform effect of cultural factors on consumer behavior towards events. Mediation analysis shows that event engagement significantly mediates the relationships between cultural characteristics such as interpersonal communication, social hierarchy, collective decision-making, and revisit intentions. Furthermore, factors like individual autonomy and social rituals directly impact revisit intentions, emphasizing their crucial roles in shaping consumer decisions at events. These findings suggest that despite regional cultural nuances, their overall impact on consumer behavior remains consistent across different settings. This research provides valuable insights into the complex interplay between culture and consumer behavior in Indonesia’s diverse socio-cultural landscape, offering practical implications for event organizers to develop universally appealing yet culturally attuned engagement strategies.